Biosurfactant as an Enhancer of Geologic Carbon Storage: Microbial Modification of Interfacial Tension and Contact Angle in Carbon dioxide/Water/Quartz Systems - Park, Taehyung; Joo, Hyun-Woo; Kim, Gyeong-Yeong; Kim, Seunghee; Yoon, Sukhwan; Kwon, Tae-Hyuk (Frontiers in Microbiology, 2017)
Injecting and storing of carbon dioxide (CO2) in deep geologic formations is considered as one of the promising approaches for geologic carbon storage (GCS). Microbial wettability alteration of injected CO2 is expected to occur naturally by microorganisms indigenous to the geologic formation or microorganisms intentionally introduced to increase CO2 storage capacity in the target reservoirs. The question as to the extent of microbial CO2 wettability alteration under reservoir conditions still warrants further investigation. This study investigated the effect of a lipopeptide biosurfactant—surfactin, on interfacial tension (IFT) reduction and contact angle alteration in CO2/water/quartz systems under a laboratory setup simulating in situ reservoir conditions. The temporal shifts in the IFT and the contact angle among CO2, brine, and quartz were monitored for different CO2 phases (3 MPa, 30°C for gaseous CO2; 10 MPa, 28°C for liquid CO2; 10 MPa, 37°C for supercritical CO2) upon cultivation of Bacillus subtilis strain ATCC6633 with induced surfactin secretion activity. Due to the secreted surfactin, the IFT between CO2 and brine decreased: from 49.5 to 30 mN/m, by 39% for gaseous CO2; from 28.5 to 13 mN/m, by 54% for liquid CO2; and from 32.5 to 18.5 mN/m, by 43% for supercritical CO2, respectively. The contact angle of a CO2 droplet on a quartz disc in brine increased: from 20.5° to 23.2°, by 1.16 times for gaseous CO2; from 18.4° to 61.8°, by 3.36 times for liquid CO2; and from 35.5° to 47.7°, by 1.34 times for supercritical CO2, respectively. With the microbially altered CO2 wettability, improvement in sweep efficiency of injected and displaced CO2 was evaluated using 2-D pore network model simulations; again the increment in sweep efficiency was the greatest in liquid CO2 phase due to the largest reduction in capillary factor. This result provides novel insights as to the role of naturally occurring biosurfactants in CO2 storage and suggests that biostimulation of biosurfactant production may be a feasible technique for enhancement of CO2 storage capacity.